2017
DOI: 10.1371/journal.pone.0173365
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices (KAP) relating to brucellosis in smallholder dairy farmers in two provinces in Pakistan

Abstract: The present study aimed to assess the extent of knowledge and understanding of brucellosis in smallholder dairy farmers and identify practices at the farm and household level that might pose a risk for humans contracting brucellosis. Between February and June 2015 a cross-sectional study was conducted among smallholder farms (n = 420) in five districts of Punjab and two districts of Sindh province. Farmers were interviewed using a questionnaire to obtain information on farmers’ knowledge about brucellosis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
67
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(103 citation statements)
references
References 25 publications
12
67
3
Order By: Relevance
“…In our results, around half of herders reported that they bury aborted fetuses and birth materials. This practice was highly prevalent (94%) among Tajikistan's dairy farmers (Lindahl et al, 2015), but not in Pakistan (Arif et al, 2017), Egypt (Hegazy et al, 2016) or…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In our results, around half of herders reported that they bury aborted fetuses and birth materials. This practice was highly prevalent (94%) among Tajikistan's dairy farmers (Lindahl et al, 2015), but not in Pakistan (Arif et al, 2017), Egypt (Hegazy et al, 2016) or…”
Section: Discussionmentioning
confidence: 98%
“…In our results, around half of herders reported that they bury aborted fetuses and birth materials. This practice was highly prevalent (94%) among Tajikistan's dairy farmers (Lindahl et al, ), but not in Pakistan (Arif et al, ), Egypt (Hegazy et al, ) or Jordan (Musallam et al, ). In our study, herders with a higher level of knowledge were more likely to correctly dispose of aborted fetuses and birth materials compared to those with a lower level of knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sampling strategies including districts, villages and farms have been described in detail by Arif et al . (). In short, two villages per district and 60 herds per village were sampled.…”
Section: Methodsmentioning
confidence: 97%
“…a farm cleaning risk score and a brucellosis herd transmission risk score, as described in a previous study on the same farmers (Arif et al . ). Briefly, the farm cleaning risk score (scored from 0 to 4) was the total number of risky practices practised by the farmer of the following four herd management practices: (1) not cleaning up dung; (2) not cleaning the feeding trough; (3) storage of dung piles for more than 6 months and, (4) not washing udder before milking.…”
Section: Methodsmentioning
confidence: 97%